Analysis of the structure of mathematical models of unsteady aerodynamic coefficients - Жила, В.Г. (Proceedings of National Aviation University (archive), 2008)
Approaches as the base for obtaining mathematic models of aerodynamic coefficients are considered. Two most complete models of unsteady aerodynamic coefficients comparable analysis is doing. Unsteady integral model of aerodynamic coefficients advantage is demonstrated.